Enhancing the Quality of Secondary Education Through Professional Development of Teachers in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
The study investigated how to enhance the quality of secondary education through professional development of teachers in Nigeria. Two research questions guided the study and one hypothesis was tested at 0.05 level of significance. The descriptive survey research design guided the study. The population of the study comprised 5396 (5,133 teachers and 263 principals) in 263 public secondary schools in six Education Zones in Anambra State. A total of 579 respondents (513 teachers and 66 principals) were drawn through proportionate stratified and simple random sampling technique for the study. Two validated structured questionnaires were used as a instrument for data collection. The application of Cronbach Alpha reliability coefficient yielded coefficient values of 0.81 for teachers’ professional development and 0.77 for quality in secondary education for the two instruments respectively with an overall coefficient value of 0.79 for internal consistency of the instrument. Mean, standard deviations and t-test were used for data analysis. The findings of the study revealed that engaging secondary school teachers in ongoing training workshops target at improving subject knowledge; establishing mentorship programmes for experienced and less experienced teachers so as to provide guidance and providing teachers with adequate time to study new techniques to improve their practice are TPD strategies for enhancing the quality of secondary education in Nigeria. The findings also show that dysfunctional school cultures, poor leadership commitment towards providing quality in secondary education, poor funding and lack of a shared vision about what high-quality instruction entails are some of the obstacles to professional development of teachers. Further findings revealed that teachers’ professional development significantly enhances the quality of secondary education in Nigeria. The researchers therefore recommended among others that Government at all levels through the ministries of education should draw up a policy framework for teachers’ professional development in secondary schools in Nigeria.